Building Partnerships and Fostering Activities to Promote English Outside the Classroom - Raluy Alonso, Ángel (Revista Alicantina de Estudios Ingleses, 2012)
Becoming proficient in at least one foreign language is a target for educational authorities throughout Europe. The question is how we can improve our students’ command of English without increasing the workload on teachers and without much funding. In El Prat de Llobregat, a city located in the vicinity of Barcelona, we have addressed that issue by creating a group of teachers, educational advisors and city council administrators, who have been acting in a coordinated way to enhance English language exposure beyond the classroom. Our interest in promoting English stems from our location: our municipality is situated next to an international airport where finding a job is bound to be dependent on English fluency. We aim to show that, through a network of members at school and administrative levels, an array of meaningful and empowering initiatives can be implemented in a city where resources are scarce and cultural backgrounds diverse.